Khat – a new precipitating factor for reversible cerebral vasoconstriction syndrome: a case report. (December 2016) - Baharith, Harith; Zarrin, Amy
Abstract Background Postpartum reversible cerebral vasoconstriction syndrome is one of the rare reversible cerebral vasoconstriction syndromes. The clinical presentation is usually characterized by recurrent headache, focal neurological deficit, and reversible cerebral vasoconstriction seen on cerebral angiography. Case presentation We report a case of a 35-year-old Yemeni woman who presented with headache and focal neurological deficits that occurred 10 days after delivery, with segmental narrowing of cerebral arteries on angiography. She had significant clinical and radiological improvement on follow-up. Conclusions The presentation of our patient's reversible cerebral vasoconstriction syndrome is unusual as she has two possible precipitating factors. In addition to being in the postpartum state, she also has a long history of chewing khat, a vasoactive substance commonly used by immigrants from Yemen. We hope that this case report will increase awareness among physicians about the use of this plant by immigrants from the horn of Africa and Yemen.